El confinamiento durante la pandemia por COVID-19: su efectividad y grado global de adherencia - Bueno-Cuadra, Roberto (2023)
This paper has as objectives to review the nature of the measures of confinement with public health purposes in general, the effectiveness of such measures, specially in the context of the COVID-19 pandemic, and the degree at which people complied with them, regarding the serious threat that COVID-19 meant. Quarantine measures can be applied to small groups, or to great populations, as it happened in the case of COVID-19 pandemic. Evidence indicates that quarantine was effective to contribute to control recent pandemics, as that of SARS and the COVID-19. However, there are many factors affecting the effectiveness of these measures, as also on the degree of compliance. On the other hand, quarantine generates important social, psychological and economic impacts on population. In spite of these pitfalls and negative impacts, quarantine keeps to be an important containment measure; therefore, its application must be accompanied by suitable assistanceto the included population.